Public acceptability of COVID-19 control measures in Singapore, Hong Kong, and Malaysia: A cross-sectional survey. (July 2022) - Voo, Teck Chuan; Ballantyne, Angela; Ng, Chirk Jenn; Cowling, Benjamin J.; Xiao, Jingyi; Phang, Kean Chang; Kaur, Sharon; Jenarun, Grazele; Kumar, Vishakha; Lim, Jane Mingjie; Tun, Zaw Myo; Wong, Nigel Chong Boon; et al.
Highlights: Public support for control measures differed in Singapore, Hong Kong, and Malaysia There is strong public support for vaccination requirements for travelers in Asia Our study highlights the impact of sociopolitical influences on public perception Public attitudes toward such control measures should be continually monitored Abstract: Background: Several countries have implemented control measures to limit SARS-CoV-2 spread, including digital contact tracing, digital monitoring of quarantined individuals, and testing of travelers. These raise ethical issues around privacy, personal freedoms, and equity. However, little is known regarding public acceptability of these measures. Methods: In December 2020, we conducted a survey among 3635 respondents in Singapore, Hong Kong, and Malaysia to understand public perceptions on the acceptability of COVID-19 control measures. Findings: Hong Kong respondents were much less supportive of digital contact tracing and monitoring devices than those in Malaysia and Singapore. Around three-quarters of Hong Kong respondents perceived digital contact tracing as an unreasonable restriction of individual freedom; <20% trusted that there were adequate local provisions preventing these data being used for other purposes. This was the opposite in Singapore, where nearly 3/4 of respondents agreed that there were adequate data protection rules locally. In contrast, only a minority of Hong Kong respondents viewed mandatory testing and vaccination for travelers as unreasonable infringements of privacy or freedom. Less than 2/3 of respondents in all territories were willing to be vaccinated against COVID-19, with a quarter of respondents undecided. However, support for differential travel restrictions for vaccinated and unvaccinated individuals was high in all settings. Interpretation: Our findings highlight the importance of sociopolitical context in public perception of public health measures and emphasize the need to continually monitor public attitudes toward such measures to inform implementation and communication strategies.